VO₂max sebagai Prediktor Kebugaran Kardiorespirasi: Studi Literatur: Ramadhana Komala, Wiwi Febriani - Komala, Ramadhana; Febriani, Wiwi (Jurnal Kedokteran Universitas Lampung, 2025)
VO₂max or maximal oxygen uptake is the main indicator of cardiorespiratory fitness that describes the body's maximum capacity to consume oxygen during physical activity. In the last decade, VO₂max has not only been used to assess physical performance, but has also been recognized as a strong predictor of morbidity and mortality from chronic diseases such as heart disease, diabetes, and cancer. Its value is greatly influenced by various factors such as age, gender, body composition, nutritional status, and physical activity. As a measure of the effectiveness of an exercise program, an increase in VO₂max reflects positive physiological adaptations, especially through structured aerobic exercise. Along with technological advances, VO₂max measurement methods are now not only limited to laboratories, but can also be done practically through field tests, non-exercise estimation models, and wearable devices based on sensors and artificial intelligence algorithms. This study concludes that VO₂max is an essential parameter in assessing fitness and health, and has great potential as a screening and monitoring tool for public health in general.